ANALYSIS OF DIVERSE HYBRIDS FOR STABILITY TO SEED YIELD AND YIELD COMPONENTS IN SUNFLOWER - RUKMINIDEVI, K.; RANGANADHA, A.R.G.; GANESH, M. (Annals of Agricultural Research, 2014)
The stability analysis of 26 hybrids developed with diverse cytoplasmic background over three environments revealed the presence of substantial interaction of the hybrids with environments. Both linear and non-linear compnents are equally important for seed yield, oil yield, oil content and filled seeds. However, the variation in the performance of the hybrids was predictable for days to 50 per cent flowering, days to maturity and 100-seed weight. Based on the environmental indices, rabi sowing of sunflower is favoured for the expression of the important characters. In general, the crosses with relatively high yield exhibited low stability indicating that the mean performance and stability are two different components. The hybrid PET-2-7-1 A x R-HR-R-2 was identified as stable hybrid for seed yield, while, PET-2-7-1A x GPA-201-1 was found suitable in favourable environments for seed yield and other components. However, the hybrid PFMS 400 A x 3376 R for oil yield and oil content while, IMS 852 x 856R was suitable for unfavourable environments for oil content and less unfilled seeds.